The Steinhaus-Weil Property: IV. Other Interior-Point Properties - Bingham, Nicholas H.; Ostaszewski, Adam J. (Sarajevo Journal of Mathematics, 2024)
ABSTRACT. In this the ﬁnal part of the four-part series [BinO3; 4,5,6] on theorems of Steinhaus-Weil type, as a companion piece to Part III, [BinO6], on Weil-type reﬁnement topologies, we study from the perspective of reﬁnement topologies the relation of the composite AB-1 to the classical setting of the AA-1 Steinhaus interior-point theorem.